RESEARCH OF DIRECTIONS FOR IMPROVING THE ACCURACY OF MANUFACTURING BLANKS FROM FOAM POLYSTYRENE - SUKHORUKOV, SERGIY; RYBIN, YEVHENII (Herald of Khmelnytskyi National University. Technical sciences, 2025)
One of the highly efficient methods of manufacturing blanks is casting using lost foam patterns. Due to small processing allowances, such blanks have a high material utilization rate. The main requirements for such models are the accuracy and quality of the resulting surfaces. In small-scale and single-piece production, blanks for casting using lost foam patterns are made of polystyrene foam using cutting with a heated wire electrode. This provides a number of advantages, namely, the cleanliness of the treated surface, the cutting speed, and the absence of fine waste. This study analyzes the current state of research into the process of cutting polystyrene foam blanks with a wire electrode. The factors analyzed by modern researchers of the process of cutting polystyrene foam blanks with a wire electrode can be divided into 3 separate groups: the influence of material properties, the influence of process parameters, and the influence of tool geometry. The largest share of factors influencing the characteristics of the process parameters are the energy parameters of the cutting process. When the heated wire and the workpiece material come into contact, heat is transferred from the wire to the workpiece in different ways: direct heat transfer, convection and radiation. It was found that the energy transfer from the heated wire to the polystyrene foam leads to both the melting and evaporation of the polystyrene foam from the contact zone and a significant decrease in the temperature of the wire itself, which over time leads to changes in the heat balance in the cutting zone. In the analyzed studies of foreign scientists, it was found that the characteristics of the workpiece material, the power of the energy supplied to the point of contact between the workpiece and the working tool and the speed of movement of the tool relative to the workpiece have the greatest influence on the energy parameters of the process. For a comprehensive study of the process of cutting polystyrene foam blanks with a wire electrode, modern researchers use the finite element method. The development of mathematical models that take into account the stretching and bending of the wire electrode during the cutting process can improve the accuracy of predicting the size of the cutting width and the geometric accuracy of the resulting workpieces.